GBL in Math Problem Solving: Is it Effective? - Pratama, Loviga Denny; Setyaningrum, Wahyu (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The present study investigates the difference effect of problem solving model with or without game-based learning (GBL) on lower and higher achievers’. Ninety-one students of grade eight (M = 13.9; SD = 0,5 year) from Indonesia were randomly allocated to participated in the study. Data were analyzed by using qualitative and quantitative methods. Two test were used in this study, one for assessing prior knowladge, and the other for the post-testing. Posttes was composed of two measuring both numeric (procedural and arithmatical accuracy) and reasoning (applied problems in geometry). Results indicated that students who were exposed to the game-based learning within problem solving (PS+GBL) significantly outperformed their counterparts who were exposed on the basis of textbook within problem solving (PS+TB). The positive effects of PS+GBL were observed on both tests of numeracy and applied problems in geometry. In addition, the findings show the positive effects of PS+GBL method on lower and higher achievers.